Induced pluripotent stem cell-derived natural killer cells gene-modified to express chimeric antigen receptor-targeting solid tumors - Ueda, Tatsuki; Kaneko, Shin (International journal of hematology, 2021)
The use of allogeneic, pluripotent stem cell-derived immune cells for cancer immunotherapy has been the subject of recent research, including clinical trials. The use of pluripotent stem cells as the source for allogeneic immune cells facilitates stringent quality control of the final product, regarding efficacy, safety, and producibility. In this review, we have described the characteristics of natural killer (NK) cells from multiple cell sources, including pluripotent stem cells, the chimeric antigen receptor (CAR)-modification method and strategy for these NK cells, and the current and planned clinical trials of CAR-modified induced pluripotent stem cell-derived NK cells.